Root crops management technology - Obordo, RA (International Center for Tropical Agriculture, 1978)
The potential and status of root crop technology (potatoes, sweet potatoes, cassava, yams, cocoyams) in Asia are described. Cassava presents the best perspectives as a low-cost energy source. In the Philippines, a surface area of 119,300 and 117,970 ha was planted to cassava with yields of 5.7 and 5.3 t/ha in 1975-76, resp. Cassava production practices, post-harvest management, marketing practices and utilization are reviewed. Research at national and international levels is presented. Currently the intention is to modify technologies for use under Asian conditions. Emphasis is placed on selecting var. adapted to acid and infertile soils (300 million ha in tropical regions of America and Asia), in the use of HI as a key factor in genetic research, the obtainment of max. yields with an optimum LAI, and in rapid propagation techniques. The main problems industries face ue indicated and the following solutions are proposed: introduction of input and management technologies; credit programs and extension services; support research on the utilization of root crops and the coordinated research oriented towards the solving of problems.Suggestions for future research are presented. The national program of root crops in the Philippines is included along with a brief descriptive work of the main crops. (CIAT)